GENETIC SIGNIFICANCE OF THE INTRALATTICE DISTRIBUTION OF OXYGEN ISOTOPES IN ALUNITES OF THE KURILE ISLANDS - Ustinov V.I.; Grinenko V.A.; Znamenskiy V.S. (My University, 1988)
In an earlier paper we have derived the methodology for the use of observational and theoretical data on the intralattice distribution of oxygen isotopes in order to solve specific genetic problems in the geochemistry of mineragenesis. For this investigation, we chose specimens from various alunite occurrences of the southern Kurile Islands. There is no systematic correlation between δ18O for alunite and hydrothermal quartz (opal). Silicate oxygen clearly is not in isotopic equilibrium with groups in alunite, which indicates above all that the alunite and silicates were formed at different times. Indeed, the alunite is a later mineral than quartz and opal (it forms stringers and replacement zones and contains inclusions of fine-grained quartz and is concentrated in cavities). Therefore, the postulate that alunite quartzes and especially alunite-containing sulfur ores are invariable members of a single metasomatic column consisting of quartz (opal), argillitized and propylite zones, is refuted.